Investigation of gray matter volume in individuals with heart failure and preserved ejection fraction - Yu, Tianyi; Bai, Qiuyun; Guo, Yiting; Yuan, Yuchun (Frontiers in Aging Neuroscience, 2025)
ObjectThis study employs voxel-based morphometry techniques to identify potential areas of brain injury in patients with heart failure with preserved ejection fraction (HFpEF). It further assesses the correlation between clinical indicators, cardiac function parameters, and gray matter volume (GMV). This provides an imaging-based anatomical biomarker for in-depth research into the brain structure in patients with HFpEF.Materials and methodsThis study recruited 51 patients with HFpEF (26 males and 25 females) and 40 healthy controls (27 males and 13 females). Data on NT-proBNP levels, echocardiographic parameters, and cognitive function scores were collected for both groups. High-resolution 3D T1-weighted imaging (3D-T1WI) structural MRI data were collected from all participants. The changes in GMV between the two groups were assessed using voxel-based morphometry (VBM).ResultsThe study involved 40 patients with HFpEF and 28 healthy controls (HC). No significant differences were observed between the groups regarding age, gender, education, or BMI. The HFpEF group exhibited larger measurements for Left Ventricular Posterior Wall (LVPW), Interventricular Septal Thickness (IVST), Left Atrial Diameter (LAD), Right Atrial Diameter (RAD), and Right Ventricular Diameter (RVD). However, they maintained preserved systolic function and achieved lower scores on the MoCA, indicating deficits in visuospatial/executive functions, naming, attention, language, and memory. Compared to HC, HFpEF patients had reduced GMV in specific brain regions. NT-proBNP levels were negatively correlated with GM reduction in various cerebellar, frontal, temporal, and postcentral regions. Cognitive performance was inversely related to GM shrinkage, with different brain regions correlating with specific cognitive deficits.ConclusionAbnormalities in GMV in several brain areas have been identified in patients with HFpEF. Furthermore, these abnormal GMV are associated with NT-proBNP levels, echocardiographic indices, and neurocognitive scoring. These observations could provide fresh perspectives on the pathogenic mechanisms of HFpEF.